ACADEMIC PERFORMANCE IN SOCIAL SCIENCES IN RELATION TO THEIR PSYCHOLOGICAL PROFILE OF THE HEARING IMPAIRED COLLEGE STUDENTS - Saladaga, Lindley L (Journal of Agriculture and Technology Management, 2012)
This study aimed to determine the Academic Performance in Social Sciences in relation to Psychological Profile of the hearing impaired college students in Cebu Technological University. This research utilized the descriptive correlation design. The respondents of the study were the 15 hearing impaired taking up Certificate of Technology course enrolled in the school year 2001-2002. The simple percentage, weighted mean were employed to determine the profile of the hearing impaired college students and the chi-square to measure the relationship. The findings of the study were: majorities (53.33 percent) of the respondents were 17 to 20 years old. Mostly (66.7 percent) were female. Most (86.68) of the hearing impaired were profound degree of hearing loss. In their academic performance, they were average. As tot the Intelligence Quotient, they were below average IQ. The respondents’ personality is average and low in self-concept. It was concluded in this study that there is no relationship between Academic Profile and Psychological Profile.